Wife Cannot Nullify Husband’s Responsibility to Provide Nafkah - Mohamad Zakky Ubaid Ermawan; Ahmad Izzudin; Mohammad Fadil Akbar Islamy (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
In the Quran, it explains that the husband has an obligation to provide Nafkah for his wife. However, in the Indonesian Islamic Law Compilation, Article 80 Paragraph 6, it is explained that a wife can nullify her husband’s obligation to provide Nafkah. That Article is used as a legal basis for husbands to instruct their wives to be the main backbone of family. This is a problem that burdens the wife. The aim of this writing is to criticize Article 80, Paragraph 6, of the Indonesian Islamic Law Compilation. So that husbands will not let go of their responsibilities. The writing method used is a literature review method. The author tries to find the legal basis for Article 80, Paragraph 6 of the Indonesian Islamic Law Compilation. The Article will be analyzed in the context of a fiqh perspective. The results of the writing can be summarized as follows: this Article has no legal basis. In fiqh, Nafkah that cannot be paid will become a debt that eventually needs to be paid later. And the wife can nullify her husband’s obligation to pay that debt. But not for the Nafkah that has not been paid yet.